Selecting Renewable Energy Sources for Small Island Using Analytical Hierarchy Process (AHP) - Emir, Fırat (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: In this modern era, energy became a necessity product in order to have a good quality in life, human development and growth in economy. However, most of the countries’ energy sectors depend on the importation of primary energy products from other countries which reduces the growth rate and the quality of life of the home country. Moreover, this dependency jeopardizes these factors. Small island countries, which are not integrated to main land, have some restrictions in their economies because of the limited primary energy resources and importation payments. Without any importation, those islands’ economies cannot sustain. However, they can find some alternative resources in order to reduce the paying money to the host countries and they can keep money inside of the country which can cause an increase in life standards for the residents. This dependence on the imported primary energy products is highly revealed to some changes in political and economic issues depending on the fluctuations in the price level. Therefore, the volatilities in fossil fuels prices and the difficulties for foreseen their prices results the risks for the consumers and suppliers. Depending on this issue, renewable energies become crucial alternative energies in order to provide clean and sustainable energy, clean environment and to protect the economy. Accordingly, the priorities of the renewable energies are appraised in this study to find out best alternative renewable energy resource for six small islands’ energy sector. AHP model is selected as a methodology for this study which gives the flexibility for the survey needed researches. The hierarchical model for the study consists of four stages which can be listed as goal, criteria, sub-criteria and the alternatives. Small island countries potentials are examined depending on the five main criteria and thirteen sub-criteria by using the AHP model in order to see the best alternative that can contribute its energy sector more than the traditional production and the other kinds of renewables. In parallel with this fact, Costs, Technical issues, Social issues, Locations and Environmental issues are evaluated as the main criteria. Moreover, thirteen subcriteria are presented for reaching this goal and analyze has been made for Malta, Cyprus, Cuba, Jamaica, Dominican Republic and Singapore separately. While the main criteria are ranked among each other, mostly the environmental factor has become the most crucial one and followed by the cost, technical, location, and social issues. The rankings in terms of the numbers can be represented as 0.378 (environmental), 0.266 (social), 0.18 (location), 0.115(technical) and 0.061(cost). Therefore; for all islands, Solar Energy is founded as the best potential in order to invest and reach goal. Furthermore, it is purposed that depending on the results and the priority of the renewable energy, the decision makers can benefit from this study in order to develop long-run policy for economic issues with respect to energy sector and create a roadmap for the energy efficiency policy for the country. Keywords: Renewable energy, sustainable development, AHP, Analytic Hierarchy Process, Small island countries. ………………………………………………………………………………………………………………………… ÖZ: Modern Çağda, enerji yaşam kalitesi, ekonomik büyüme ve insan gelişim için zorunlu hale gelmiştir. Fakat çoğu ülkelerin enerji sektörünün diğer ülkelerden yapılan birincil enerji ithalatına bağlı olması, ülkedeki ekonomik büyüme oranını ve yaşam kalitesini azaltmaktadır. Ana karaya entegre olmayan küçük ada ülkelerinin enerji ithal eder durumda oluşu onların ekonomik büyümesinin ve ithalat ödemelerinin önünde bazı kısıtlamalara sebep olmaktadır. Herhangi bir enerji ithalatı olmadan bu adaların ekonomik sürdürülebilirliği imkânsız hale gelmektedir. Ancak bazı alternatifler bularak dış ödemelere azaltmak ve ülke içerisinde parayı tutmak ülkedeki yaşam kalitesi artırımına neden olabilir. Bu ülkelerin enerji sektörleri genelde dış ülkelerde yapılan fosil yakıtlarının ithaline bağlıdır. Birincil enerji ürünleri üzerine olan bu bağımlılık fiyat seviyelerindeki yüksek dalgalanmalara sebep olup bazı siyasi ve ekonomik konularda değişikliklere sebebiyet verebilir. Bu konuya bağlı olarak, bu çalışmada, enerji sektörü için alternatife yenilenebilir enerji kaynakları değerlendirilmiş ve en iyi yenilenebilir enerji kaynağını bulmak amacıyla öncelikleri belirlenmiştir. Bu çalışma için, anket gerekli araştırmalar için esneklik gösteren, yöntem olarak Analitik Hiyerarşi Süreci seçilmiştir. Buna bağlı olarak, yapılan bu çalışma için AHS modelinin hiyerarşik modeli amaç, kıstaslar, alt kıstaslar ve alternatifler olarak dört aşama şeklinde belirlenmiştir. Küçük ada ülkeleri potansiyelleri arasından enerji sektörüne daha çok katkı sağlayabilecek olan en iyi alternatifi seçmek için AHS kullanılanılmış ve beş ana ve on üç alt kıstasa bağlı olarak potansiyeller değerlendirilmiştir. Bu esasa bağlı olarak, maliyetler, teknik konular, sosyal konular mekân ve çevre konuları ana kıstaslar olarak değerlendirilmiştir. Dahası, bu hedefe ulaşmak için onüç alt kıstas kullanılarak Malta, Kıbrıs, Küba, Jamaika, Dominik Cumhuriyeti ve Singapur için ayrı ayrı analiz edilmiştir. Ana kıstaslar birbirleri arasında değerlendirildiğinde, en öncelikli olarak çevresel konular gelmiştir ve önem sırası sosyal, mekan, teknik ve maliyet konuları olarak sıralanmıştır. Sayısal olarak değerlendirildiğinde, 0,378 olarak çevre birinci sırada gelmekte 0,266 ile sosyal, 0,18 ile mekân, 0,115 ile teknik ve 0,061 ile maliyet önem sırası taşımaktadır. Bunun yanında, güneş enerjisi tüm ada ülkelerinde amaca ulaşmak için en uygun yatırım potansiyeli olarak seçilmiştir. Böylelikle, bu çalışmanın, sonuçları ve ve elde edilen önem dereceleri ışığında, karar vericiler için bu çalışma, uzun dönemli enerji sektörüne bağlı ekonomik politikalar için kullanılabilir kaynak olması ve enerji verimliliği için yol haritası oluşturabilir bir araştırma olması amaçlanmıştır. Anahtar Kelimeler: Yenilenebilir Enerji, sürdürülebilir kalkınma, AHS, Analitik hiyerarşi süreci, Küçük Ada Ülkeleri.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2014. Supervisor: Prof. Dr. Mehmet Balcılar.
Keywords: Economics; Renewable energy sources; Energy Economics; Energy Conservation - Power Resources - Economics; Renewable Energy, Sustainable Development, AHP, Analytic Hierarchy Process, Small Island Countries